Single molecule tracking reveals spatio-temporal dynamics of bacterial DNA repair centres. Issue 1 (December 2018) - Rösch, Thomas; Altenburger, Stephan; Oviedo-Bocanegra, Luis; Pediaditakis, Miriam; Najjar, Nina; Fritz, Georg; Graumann, Peter
Abstract Single-particle (molecule) tracking (SPT/SMT) is a powerful method to study dynamic processes in living bacterial cells at high spatial and temporal resolution. We have performed single-molecule imaging of early DNA double-strand break (DSB) repair events during homologous recombination in the model bacteriumBacillus subtilis . Our findings reveal that DNA repair centres arise at all sites on the chromosome and that RecN, RecO and RecJ perform fast, enzyme-like functions during detection and procession of DNA double strand breaks, respectively. Interestingly, RecN changes its diffusion behavior upon induction of DNA damage, from a largely diffusive to a DNA-scanning mode, which increases efficiency of finding all sites of DNA breaks within a frame of few seconds. RecJ continues being bound to replication forks, but also assembles at many sites on the nucleoid upon DNA damage induction. RecO shows a similar change in its mobility as RecN, and also remains bound to sites of damage for few hundred milliseconds. Like RecN, it enters the nucleoid in damaged cells. Our data show that presynaptic preparation of DSBs including loading of RecA onto ssDNA is highly rapid and dynamic, and occurs throughout the chromosome, and not only at replication forks or only at distinct sites where many breaks are processes in analogy to eukaryotic DNA repair centres.